2020
DOI: 10.1016/j.mayocp.2019.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Treatment of Overactive Bladder in Women

Abstract: Overactive bladder (OAB) is a symptom complex that includes urinary urgency, frequency, urgency incontinence, and nocturia. It is highly prevalent, affecting up to 12% of the adult population, and can significantly impact quality of life. The diagnosis of OAB is made by history, physical examination, and a urinalysis to rule out underlying infection or other concerning potential etiologies. The need for additional testing is based on the initial evaluation findings, and is recommended in cases of underlying ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
58
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 31 publications
0
58
0
2
Order By: Relevance
“…[ 2 , 3 ] It is reported that 3.4% of men and 8.7% of women aged from 40 to 44 years old would have symptoms of OAB, and more than 80% of individuals aged 80 to 90 years may have at least one void per night. [ 4 6 ] As the globe is expected to step into old-age society, the OAB is likely to place an increasing strain on healthcare resources. Anticholinergic agents, [ 7 ] such as solifenacin and tolterodine, are used as the cornerstone of pharmacotherapy for OAB symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…[ 2 , 3 ] It is reported that 3.4% of men and 8.7% of women aged from 40 to 44 years old would have symptoms of OAB, and more than 80% of individuals aged 80 to 90 years may have at least one void per night. [ 4 6 ] As the globe is expected to step into old-age society, the OAB is likely to place an increasing strain on healthcare resources. Anticholinergic agents, [ 7 ] such as solifenacin and tolterodine, are used as the cornerstone of pharmacotherapy for OAB symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the vaginal route has several advantages such as high permeability to many drugs, avoidance of first-pass hepatic metabolism, and the suitability to accommodate relatively large doses [ 30 ]. A delivery system could be used to treat overactive bladder and vaginal dryness simultaneously, which are common issues faced by human females after menopause [ 31 ]. However, it is obviously limited to females as well as being associated with local irritation and variability in the extent and rate of drug absorption [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are several alternatives for OAB and UI treatment: behavioral treatments, considered first-line treatments; pharmacological or second-line treatments such as anticholinergic or antimuscarinic and b-adrenergic drugs, and, by way of a third line of treatment, injections of OnabotulinumtoxinA and therapies with electrical stimulation, including, among others, percutaneous and transcutaneous electrical stimulation (PTNS and TTNS, respectively), which are the object of this study [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…With regard to treatment by electrical stimulation of the posterior tibial nerve (PTN), this involves retrograde stimulation of the nerve fibers of the sacral plexus, which innervates the bladder and detrusor muscle [ 2 , 3 , 4 , 5 , 8 ]. Electrical stimulation can be applied through insertion of a needle in the PTN—that is, PTNS is carried out in the said nerve—or through surface electrodes, with TTNS [ 9 ], with beneficial and safe effects in the short term in women with OAB, and no relevant adverse effects [ 10 ], according to the review by Sousa-Fraguas et al, 2020.…”
Section: Introductionmentioning
confidence: 99%